Impact of Intracellular Glutathione Depletion on Neutral Sphingomyelinase in Human Hepatoma HepG2 cells - Tanios, Marie (AUC Knowledge Fountain, 2021)
Introduction: Incidence of hepatocellular carcinoma (HCC) has been increasing dramaticallyandliver cancer is the fifth most common cancer globally. Increasing sphingomyelin (SM) hydrolysis via activation of the cell surface membrane-associated neutral sphingomyelinase (nSMase) has been linked to cell proliferation and apoptosis. Glutathione (GSH) depletion was reported to mediate induction of apoptosis via nSMase activation. On the other hand, other studies reported that GSH protected cancer cells against apoptosis. We hypothesized that GSH synthesis inhibition with buthioninesulfoximine (BSO) increases HepG2 cell proliferation. Objectives: The aim of the current study wasto investigate the effect of GSH depletion using BSO on HepG2 cell proliferation through evaluating nSMase mRNA expression and enzymaticactivity levels in addition to ceramide content. Methods: nSMase activity was assessed using Amplex red sphingomyelinase fluorescence assay. nSMases mRNA expression was assessed by real-time PCR. Finally, ceramide content was evaluated using ceramide colorimetric assay. Results: Our findings demonstrated that GSH synthesis inhibition using BSO decreases nSMase activity in HepG2 and was not accompanied by ceramide generation. In addition, results show that nSMase 1 and 3 expressions were upregulated, while nSMase 2 was not expressed in HepG2 cells. Furthermore, and despite GSH synthesis inhibition, BSO stimulated HepG2 cellular proliferation possibly through its inhibitory effect on nSMase activity. Conclusion: Our study demonstrated that one-third of total nSMase, nSMase 2, is not expressed in HepG2 cells and the activities of the nSMase 1 and 3 are inhibited through BSO treatment, this explains why cellular proliferation was expected despite the high oxidative stress the cells were subjected to. We postulate that ceramide is an important molecule in inducing apoptosis in HepG2 cells; therefore, it is crucial to activate and increase the function of nSMase enzymes.